2023
DOI: 10.3390/jfb14100526
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of an Isocyanate Structure on a Polyurethane Delivery System for 2′-Deoxycytidine-5′-monophosphate

Florin Borcan,
Titus Vlase,
Gabriela Vlase
et al.

Abstract: The delivery of nucleosides represents an interesting research trend in recent years due to their application in various viral infections. The main aims of this study were to develop and to characterize polyurethane particles that are intended to be used for the transport of nucleosides. Three samples have been prepared using aliphatic diisocyanates, a mixture of polyethylene glycol, polycaprolactone, and diols, respectively. The samples were characterized through refractivity measurements, drug loading effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…In the current study, the highest value was registered for the second sample, with GDA (67.8%); a value that is comparable to those reported in the literature [21,23]. The DCSS release profile from PU microstructures that were maintained in SBF medium exhibited a fast phase in the first 20 h and then the cumulative percentage increased slowly from 47 to 58% (sample_1) and from 51 to 61% (sample_2) in the next 24 h. It must be noted that the degradation of PU microstructures and their release profile can be easily modified by using various polyether/polyester ratios in their synthesis [23].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the current study, the highest value was registered for the second sample, with GDA (67.8%); a value that is comparable to those reported in the literature [21,23]. The DCSS release profile from PU microstructures that were maintained in SBF medium exhibited a fast phase in the first 20 h and then the cumulative percentage increased slowly from 47 to 58% (sample_1) and from 51 to 61% (sample_2) in the next 24 h. It must be noted that the degradation of PU microstructures and their release profile can be easily modified by using various polyether/polyester ratios in their synthesis [23].…”
Section: Discussionsupporting
confidence: 89%
“…The proliferation and adhesion of various cells to polymer biomaterials such as polyethyleneimine, polypropyleneimine, polypyrrole, and poly(p-phenylenediamine) were reported two decades ago [ 41 ]. Zanetta et al [ 42 ] have found that PU foams can be used as a support material for the proliferation of mesenchymal stem cells, while our previous study has revealed the same behavior [ 23 ]. In the current research, the cell viability data demonstrate the compatibility of the carrier with the cellular environment and highlight the fact that PU microstructures at the tested concentration are suitable as a delivery system for DCSS.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…A very versatile biomaterial used in medical applications such as catheters, wound dressings, coatings, and drug delivery systems is represented by polyurethane (PU) [23][24][25][26], in particular by thermoplastic PU (TPU). This polymer is composed of soft and hard segments, polyols and isocyanates, respectively [24,26], whose proportions determine a different degree of flexibility, toughness, and softness [23] and confer good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%